From Russia with code : programming migrations in post-Soviet times - Biagioli, Mario; Lépinay, Vincent Antonin (Duke University Press, 2019)
While Russian computer scientists are notorious for their interference in the 2016 US presidential election, they are ubiquitous on Wall Street and coveted by international IT firms and often perceive themselves as the present manifestation of the past glory of Soviet scientific prowess. Drawing on over three hundred in-depth interviews, the contributors to From Russia with Code trace the practices, education, careers, networks, migrations, and lives of Russian IT professionals at home and abroad, showing how they function as key figures in the tense political and ideological environment of technological innovation in post-Soviet Russia. Among other topics, they analyze coders' creation of both transnational communities and local networks of political activists; Moscow's use of IT funding to control peripheral regions; brain drain and the experiences of coders living abroad in the United Kingdom, United States, Israel, and Finland; and the possible meanings of Russian computing systems in a heterogeneous nation and industry. Highlighting the centrality of computer scientists to post-Soviet economic mobilization in Russia, the contributors offer new insights into the difficulties through which a new entrepreneurial culture emerges in a rapidly changing world.Contributors. Irina Antoschyuk, Mario Biagioli, Ksenia Ermoshina, Marina Fedorova, Andrey Indukaev, Alina Kontareva, Diana Kurkovsky, Vincent Lépinay, Alexandra Masalskaya, Daria Savchenko, Liubava Shatokhina, Alexandra Simonova, Ksenia Tatarchenko, Zinaida Vasilyeva, Dimitrii Zhikharevich